DETERMINANTS OF THE IMPLEMENTATION OF EARLY BREASTFEEDING INITIATION (IMD) IN THE WORKING AREA OF THE PONDOK CABE ILIR HEALTH CENTER IN 2022 - Ghina Az Zahra; Siti Riptifah Tri Handari (Muhammadiyah International Public Health and Medicine Proceeding, 2023)
The incidence of dysmenorrhea in Indonesia has reached 64.5%, based on a survey conducted at one school in Garut Regency, as many as 60-70% of female students experienced primary dysmenorrhea. This study aimed to determine the relationship between the age of menarche, menstrual cycle, family history, physical activity, frequency of fast food consumption, and history of exposure to cigarette smoke with the incidence of primary dysmenorrhea. The method in this research uses cross-sectional with a total sample of 176 samples determined using stratified random sampling by determining probability using probability proportional to size then tested univariately and bivariately using Chi Square with α = 0.05. The results of the study showed that factors associated with the incidence of primary dysmenorrhea included age at menarche, family history, frequency of fast food consumption, physical activity, and history of exposure to cigarette smoke. Meanwhile, the menstrual cycle is not related to the incidence of primary dysmenorrhea. Suggestions that researchers can give include students being more careful and aware of themselves to prevent primary dysmenorrhea.